Enhancing Laboratory Safety Culture: Data-Driven Risk Management in Metal Powder Laboratories - Thabit, Ahmed (My University, 2024)
The aim of this thesis is to discuss data-driven risk management for improving laboratory safety culture in metal powder laboratories. This has necessitated the adoption of a mixed-method methodology for in-depth analysis of both environmental conditions and safety practices. Quantitative information on the laboratory's every vital parameter was collected on a real-time basis using highly accurate sensors for temperature, humidity, and level of particulate matter PM10, PM2.5, PM 100. Qualitative information was gathered from semi-structured interviews from laboratory assistants, pointing at perceived risks, safety practices, and necessary improvements. The results show that though the temperature remains constant in the lab, the high level of humidity may affect the nature of the metal powders and even laboratory safety. The extreme fluctuation and multi-peak of PM concentration shows that some operations are possible safety hazards. The correlation analysis performed indicates a complicated interaction of environmental variables and particulate matter concentration, thus requiring an integrated approach in managing risks. The theme analysis of the responses of laboratory assistants underlines the importance of keeping the same level in safety, especially the use of PPE. At the same time, it points out some points that require improvement, such as fire safety and deeper training in safety issues. Merging sensor data with qualitative data underlines the capability of data-driven approaches to enhance safety and foster an active safety culture. This study furthers the field by demonstrating how quantitative data analysis, in conjunction with qualitative insights, can be used to enhance laboratory safety. The paper provides a framework for using real-time monitoring and data analytics to identify and mitigate risks, with a novel approach to promoting safety culture in metal powder laboratories. Proposed interventions include the installation of real-time monitoring systems, the development of improved safety training programs, and routine maintenance of safety equipment. Future research should focus on advanced data analytics and the assessment of long-term effects of improved safety protocols on laboratory safety culture.

Tämän opinnäytetyön tavoitteena on käsitellä datalähtöistä riskinhallintaa laboratorioturvallisuuskulttuurin parantamiseksi metallijauhelaboratorioissa. Tämä on edellyttänyt sekamenetelmien käyttöönottoa sekä ympäristöolosuhteiden että turvallisuuskäytäntöjen syvälliseen analysointiin. Kvantitatiivista tietoa laboratorion kaikista elintärkeistä parametreista kerättiin reaaliajassa käyttämällä erittäin tarkkoja lämpötila-, kosteus- ja hiukkaspitoisuuksia PM10, PM2.5, PM 100 mittaavia antureita. Laadullista tietoa kerättiin laboratorion puolistrukturoiduista haastatteluista. avustajia, jotka osoittavat havaitut riskit, turvallisuuskäytännöt ja tarvittavat parannukset. Tulokset osoittavat, että vaikka lämpötila pysyy laboratoriossa vakiona, korkea kosteustaso voi vaikuttaa metallijauheiden luonteeseen ja jopa laboratorion turvallisuuteen. Hiukkaspitoisuuden äärimmäinen vaihtelu ja monihuippu osoittavat, että jotkut toiminnot ovat mahdollisia turvallisuusriskejä. Suoritettu korrelaatioanalyysi osoittaa ympäristömuuttujien ja hiukkaspitoisuuden monimutkaisen vuorovaikutuksen, mikä edellyttää integroitua lähestymistapaa riskien hallinnassa. Laboratorioiden vastausten teemaanalyysi korostaa turvallisuuden, erityisesti henkilönsuojainten käytön, säilymisen merkitystä. Samalla se tuo esiin joitain kehittämistä vaativia kohtia, kuten paloturvallisuuden ja turvallisuusasioiden syventämisen. Anturidatan yhdistäminen laadulliseen dataan korostaa tietopohjaisten lähestymistapojen kykyä parantaa turvallisuutta ja edistää aktiivista turvallisuuskulttuuria. Tämä tutkimus edistää alaa osoittamalla, kuinka kvantitatiivista data-analyysiä yhdessä laadullisten oivallusten kanssa voidaan käyttää laboratorioturvallisuuden parantamiseen. Paperi tarjoaa puitteet reaaliaikaisen seurannan ja data-analytiikan käytölle riskien tunnistamiseen ja lieventämiseen uudenlaisen lähestymistavan avulla turvallisuuskulttuurin edistämiseen metallijauhelaboratorioissa. Ehdotettuihin toimenpiteisiin kuuluvat reaaliaikaisten valvontajärjestelmien asentaminen, parannettujen turvallisuuskoulutusohjelmien kehittäminen ja turvalaitteiden rutiinihuolto. Tulevaisuuden tutkimuksen tulee keskittyä kehittyneeseen data-analytiikkaan ja parannettujen turvallisuuskäytäntöjen pitkän aikavälin vaikutusten arviointiin laboratorioturvallisuuskulttuuriin.
Keywords: risk management; industrial safety; laboratories; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Systems Analytics